Scaphosepalum manningii Luer (Orchidaceae: Pleurothallidinae), a new species for Costa Rica - Dalström, Stig (Lankesteriana: International Journal on Orchidology, 2015)
A species previously known from a single collection in Venezuela; Scaphosepalum manningii was recently discovered in the Boracayan forest reserve in southwestern Costa Rica. It is here illustrated and compared with a closely related and, for Costa Rica, possibly sympatric species; Scaphosepalum clavellatum.